Aula de leitura: representações em jogo na constituição do sujeito-leitor - Bizzotto, Mírian Pereira Gautério (2006)
This research had as objective to make a survey of a student-teacher´s reading representations, in the initial years of the elementary school, in order to verify if the reading is dealt as a moment for the production of meaning. It also aimed to interpret and discuss the sayings that constitute the speech of the pupil-teacher about the reading practices and the possible ethical consequences of these discourses about the formation of the students in the Third Grade. As aim, this research was based on the following questions: what are the representations on reading that can be perceived in the sayings of the pupil-teacher participants? What are the readings conceptions that can be noticed regarding the participant´s speech? What are the possible ethical and political consequences of an approach based on conceptions extracted from their sayings? In order to make this discussion possible, the concept of representation based on Woodward (2000) and Silva (2000) was considered. Furthermore, the process of reading was dealt by regarding its different schools of thought. Also, themes such as identity, difference and identification were approached. In order to collect the data, a semi-structured interview for the student-teacher, classroom observations with audio recordings and field notes were used. Given the data analysis, it became clear that the reading is viewed as a mean to reach the writing skills and also, that reading is a way to extract just one meaning, the one authorized by the teacher. The text is viewed as an object that carries a meaning to be singled out. In this perspective, the reader is viewed as a passive agent, and is not capable of building meanings, but is capable of extracting the meanings in the surface of the text. The text is emphasized, closed, and keeps the meaning. This research proves the hypothesis that the reading has not been treated as a space for the meaning production, because the teacher´s reading practice is resultant of the representations from which he or she is constituted, having a direct impact over his/her work, does not presupposes the reader as a producer of meaning, as an ideologically positioned individual, influenced by the unconscious. Given the data analysis and discussion, it is believed that the teacher needs to work with the possibility of multiple readings, not only one of them. To conclude, the practice is a result of representations, and it is necessary that a reading policy should be implemented in order to promote immediate modifications starting from the beginning of school life. Therefore, the reading practice must be reviewed, rethought, renewed, in order to be implemented inside the classrooms, changing the education focus to the student-reader, which is the meaning producer.